2021
DOI: 10.3389/fcell.2021.671698
|View full text |Cite
|
Sign up to set email alerts
|

An Insight Into the Mechanism of Plant Organelle Genome Maintenance and Implications of Organelle Genome in Crop Improvement: An Update

Abstract: Besides the nuclear genome, plants possess two small extra chromosomal genomes in mitochondria and chloroplast, respectively, which contribute a small fraction of the organelles’ proteome. Both mitochondrial and chloroplast DNA have originated endosymbiotically and most of their prokaryotic genes were either lost or transferred to the nuclear genome through endosymbiotic gene transfer during the course of evolution. Due to their immobile nature, plant nuclear and organellar genomes face continuous threat from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 256 publications
(366 reference statements)
0
11
0
Order By: Relevance
“… 30 , 31 , 44 WHY2 protein in potato and WHY1 and WHY3 proteins in Arabidopsis are also involved in maintaining low mutation rates and structural integrity of mitochondrial and chloroplast genomes. 27 , 28 , 29 , 45 The crystal structure of Solanum tuberosum WHY2, a close homolog of Arabidopsis WHY2, revealed that WHIRLY proteins bind to single-strand DNA to promote accurate repair of DNA double-strand breaks over an error-prone repair pathway 29 . We supposed that the allocation of WHY2 between cytoplasm and plastid by UPL5 is involved in maintaining plastid genome stability.…”
Section: Resultsmentioning
confidence: 99%
“… 30 , 31 , 44 WHY2 protein in potato and WHY1 and WHY3 proteins in Arabidopsis are also involved in maintaining low mutation rates and structural integrity of mitochondrial and chloroplast genomes. 27 , 28 , 29 , 45 The crystal structure of Solanum tuberosum WHY2, a close homolog of Arabidopsis WHY2, revealed that WHIRLY proteins bind to single-strand DNA to promote accurate repair of DNA double-strand breaks over an error-prone repair pathway 29 . We supposed that the allocation of WHY2 between cytoplasm and plastid by UPL5 is involved in maintaining plastid genome stability.…”
Section: Resultsmentioning
confidence: 99%
“…Although the plant plastid transformation has been successful, there are also limitations associated with its use, such as the frequent inability to obtain progeny harboring the transgene, as well as the need for specialized instruments ( Piatek et al, 2018 ; Arimura et al, 2020 ). Importantly, organellar genome editing might now be achievable by expressing genes encoding sequence-specific nucleases in the organelles or in the nucleus ( Mahapatra et al, 2021 ; Hanson et al, 2013 ). The introduction of a transgene into the mitochondrial or chloroplast genome is mediated by homologous recombination and thus relies on DSB formation in the organellar genome ( Li et al, 2021a ; Mahapatra et al, 2021 ).…”
Section: Editing Of Plant Organellar Genomesmentioning
confidence: 99%
“…Importantly, organellar genome editing might now be achievable by expressing genes encoding sequence-specific nucleases in the organelles or in the nucleus ( Mahapatra et al, 2021 ; Hanson et al, 2013 ). The introduction of a transgene into the mitochondrial or chloroplast genome is mediated by homologous recombination and thus relies on DSB formation in the organellar genome ( Li et al, 2021a ; Mahapatra et al, 2021 ). Genome editing based on the sequence-specific nucleases ZFNs, TALENs, and CRISPR/Cas9 leads to precise DSBs that may therefore increase the efficiency of genome editing in these plant organelles.…”
Section: Editing Of Plant Organellar Genomesmentioning
confidence: 99%
“…Plant genetic information is distributed among nuclear, plastid and mitochondrial genomes ( Mahapatra et al., 2021 ; Camus et al., 2022 ), and genetic markers for each genome provide complementary tools for investigations of inheritance and evolution ( Qiu et al., 1999 ; Duminil and Besnard, 2021 ; Besse, 2021 ; Camus et al., 2022 ). Although genome sequencing is the gold standard for such studies, convenient PCR-based markers retain utility and appeal ( Egan et al., 2012 ; Hodel et al., 2016 ; Besse, 2021 ).…”
Section: Introductionmentioning
confidence: 99%